Translation and Analysis of Tboli Folktales: Basis for Developing a Localized Module - ALINSUGAY, LORAINE ROSE (International Journal of Arts, Sciences and Education, 2025)
The literary works until now remain in the books or spoken by the tribal elders. Before the Spaniards arrived in the Philippines, there were already various stories in the country. This research aimed to collect Tboli folktales and translated this in Filipino language. The translated folktales were the basis for developing a localized module. Teachers and studentsts act as respondents chosen through Purposive Sampling. It aimed to evaluate the translated texts and module based on clarity, grammar, rhetorical correctness, utility, and overall appropriateness, as well as how teachers and students perceived the module. The results indicated that students showed a very strong proficiency in Tboli Folktales, and the module was well accepted in terms of objectives, content, and design. Teachers and students did not have much difference in their acceptability of the module. Overall, the study determined that the translation of Tboli Folktales from the indigenous language into Filipino enhanced the comprehensibility of the text by the students and promotes greater appreciation of the culture and language. The study suggests the adoption of the developed localized module by other schools and local languages in the Philippines, in addition to the provision of extra training for teachers to enhance the quality of language-based instruction.